#### Answer

Net change is 27

#### Work Step by Step

$h(t) = t^2 + 5$
$h(-3) = (-3)^2 +5 = (9) +5 = 14$
$h(6) = (6)^2 + 5 = (36) + 5 = 41$
$h(6) - h (-3) = 41 - 14 = 27$
Net change is an increase by 27

Published by
Brooks Cole

ISBN 10:
1305071751

ISBN 13:
978-1-30507-175-9

Net change is 27

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.